Nocturnal periodic limb movements decrease antioxidant capacity in post‐stroke women. (2nd June 2015) - Chen, C.‐Y.; Yu, C.‐C.; Chen, C.‐L.
Abstract : Objectives: Considerable evidence suggests that periodic limb movements during sleep (PLMS) are associated with cardiovascular risk and poor stroke outcome. However, the pathogenesis for this association in stroke patients remains largely unknown. Materials and Methods: This cross‐sectional study enrolled 112 consecutive patients who were admitted to rehabilitation ward due to ischemic stroke. Polysomnography and laboratory tests for oxidative stress and inflammatory biomarkers including C‐reactive protein, interleukin 6, total antioxidant capacity (TAC), and urinary 8‐hydroxy‐2‐deoxyguanosine were conducted. Results: Patients were stratified into three categories according to their PLMS index. Patients in the PLMS index ≥15 group were significantly older ( P  =   0.011), presented a significantly higher National Institute of Health Stroke Scale at stroke onset ( P  =   0.032), and lower Barthel index ( P  =   0.035) than patients in the PLMS index <5 group. The level of TAC differed significantly ( P  =   0.018) among the three groups. Multivariate linear regression analyses show that the PLMS index was negatively and independently correlated with TAC ( P  =   0.024) in women. Besides, multivariate logistic regression analyses also reveal that patients with a PLMS index ≥15 compared with the referent PLMS index <5 had a 7.58‐fold increased relative hazard for stroke recurrence (odds ratio 7.58, [1.31–43.88], P  =   0.024). Conclusions: This study suggests that PLMS was independently associated with decreased antioxidant capacity in women with ischemic stroke.